2021
DOI: 10.3389/fcell.2021.639321
|View full text |Cite
|
Sign up to set email alerts
|

Novel Long Non-coding RNA Expression Profile of Peripheral Blood Mononuclear Cells Reveals Potential Biomarkers and Regulatory Mechanisms in Systemic Lupus Erythematosus

Abstract: ObjectiveThe multisystem involvement and high heterogeneity of systemic lupus erythematosus (SLE) lead to great challenges in its diagnosis and treatment. The purpose of this study was to find new lncRNAs in peripheral blood mononuclear cells of SLE patients by transcriptome sequencing and explore their potential as biomarkers and their correlation with clinical features.Materials and MethodsTranscriptome sequencing was used to screen differentially expressed lncRNAs (DELs) and mRNAs (DEMs). The expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
(61 reference statements)
5
13
0
Order By: Relevance
“…The results indicated that these common DEGs may lead to the occurrence and development of SLE. Previous studies had shown that lncRNA and circRNA are important factors leading to the occurrence of SLE ( Cheng et al, 2021 ; Jiang et al, 2021 ). We found that the differential expression of these common DEGs might play an important role in this process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicated that these common DEGs may lead to the occurrence and development of SLE. Previous studies had shown that lncRNA and circRNA are important factors leading to the occurrence of SLE ( Cheng et al, 2021 ; Jiang et al, 2021 ). We found that the differential expression of these common DEGs might play an important role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…GSE162828 included 10 samples of peripheral blood mononuclear cells and was divided into the SLE group (5 samples) and healthy controls group (5 samples). GSE169080 included seven samples of peripheral blood mononuclear cells and was divided into SLE group (4 samples) and healthy controls group (3 samples) ( Clough and Barrett, 2016 ; Cheng et al, 2021 ; Jiang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We proposed that NONHSAT101022.2 may exacerbate SLE by promoting NK cells to secrete IFN‐γ by cis‐regulating LMBRD2 (LMBR1 Domain Containing 2) to amplify the β2‐AR signal transduction. Further functional experiments need to be performed 82 …”
Section: Lncrnas In Peripheral Blood and Bone Marrow Samples From Slementioning
confidence: 99%
“…The expression of lncRNAs directly affects in the occurrence and development of SLE and may be related to organ damage, clinical symptoms, and changes in biomarkers of disease activity and progression. The downregulation of the lncRNA NONHSAT101022.2 in the peripheral blood of SLE patients may increase β2-AR signal transduction via cis-regulation of LMBRD2, thereby inducing natural killer cells to produce high levels of IFN-γ and worsening the progression of SLE ( 84 ). The expression of AC007278.2 continues to increase in the peripheral blood of SLE patients, which regulates autoimmunity and follicular T helper cell differentiation by affecting the expression of CCR7, AZU1, and TNIP3 ( 85 ).…”
Section: Candidate Rnas As Sle Biomarkersmentioning
confidence: 99%